2010
DOI: 10.1111/j.1440-172x.2010.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

A chance to live: Women's experiences of living with a colostomy after rectal cancer surgery

Abstract: The aim of this study was to describe women's experience of living with a colostomy after rectal cancer surgery. Interviews with five women about their experiences were subjected to thematic content analysis. The findings showed that receiving a cancer diagnosis gave rise to thoughts about life and death. For the women to feel comfortable, the information and health-care measures need to focus on supporting them through the entire process, also when the treatment is completed. After the surgery, the women adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 37 publications
1
54
0
5
Order By: Relevance
“…Changes in physical status were the primary stressor type for temporary colostomy patients; this finding was similarly observed among permanent colostomy patients in Taiwan and in another study (Tseng et al, ; Zamanzadeh, Valizadeh, Rahmani, Zirak, & Desiron, ). Approximately 52% of the participants reported that they had uncertainty about waiting for the colostomy closure time and CRC recurrence, similar to previous findings in other studies (Andersson et al, ; Danielsen et al, ). Stoma closure means the current treatment to a new stage for his cancer survival.…”
Section: Discussionsupporting
confidence: 87%
“…Changes in physical status were the primary stressor type for temporary colostomy patients; this finding was similarly observed among permanent colostomy patients in Taiwan and in another study (Tseng et al, ; Zamanzadeh, Valizadeh, Rahmani, Zirak, & Desiron, ). Approximately 52% of the participants reported that they had uncertainty about waiting for the colostomy closure time and CRC recurrence, similar to previous findings in other studies (Andersson et al, ; Danielsen et al, ). Stoma closure means the current treatment to a new stage for his cancer survival.…”
Section: Discussionsupporting
confidence: 87%
“…Understanding of this experience is deepened by the exploration of how bodily mastery is achieved and experienced over a longer time-frame than used in previous studies, highlighting the centrality of relationships with healthcare staff responsible for building competence in stoma self-care. Experiences of appliance failure, unscheduled or audible bowel movements or a perception that others can see the stoma impinge on individuals' self-confidence and social function [11,41,42]. However, there is a lack of recognition of the importance of these elements of bodily mastery in supporting the development of self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considering that many of the participants received an ostomy 10 years ago on average, inappropriate family support could have bothered the patients or lowered their self‐esteem, with increases in the ostomy care duration . In particular, sexual problems in ostomy patients have been highlighted in multiple studies as an important issue in their spousal relationships …”
Section: Discussionmentioning
confidence: 99%